Tussen liefhebbers en professionals. Het "groene tijdschrift", 1978-2007 - Vermij, Rienk (Studium, 2019)
Gewina, the Dutch society for the history of science and medicine, started a newsletter in 1957. In 1978, this was converted into an official journal, Tijdschrift voor de Geschiedenis der Geneeskunde, Natuurwetenschappen, Wiskunde, en Techniek. Initially it was published by Rodopi in Amsterdam, but in 1992 it went over to Erasmus Publishing in Rotterdam under the new name of Gewina. The journal was to serve both the interests of the members of the society, who were mostly amateurs, especially from the medical profession, and the promotion and professionalization of the history of science and medicine in the academic world. These two objectives appeared hard to reconcile. Because of the increasing application of academic standards, the medical amateurs felt increasingly less at home. On the other hand, developments in scientific publishing and increasing burocratic tendencies at the universities put the right to existence of a Dutch-language journal into question in the academic world as well. In 2007, the society decided to join forces with some other Dutch and Belgian societies. This led to the end of Gewina and the start of the new journal Studium.